Instructional Utility and Learning Efficacy of Common Active Learning Strategies. Issue 4 (1st November 2017) - McConnell, David A.; Chapman, LeeAnna; Czajka, C. Douglas; Jones, Jason P.; Ryker, Katherine D.; Wiggen, Jennifer
ABSTRACT: The adoption of active learning instructional practices in college science, technology, engineering, and mathematics (STEM) courses has been shown to result in improvements in student learning, contribute to increased retention rates, and reduce the achievement gap among different student populations. Descriptions of active learning strategies have been reported in other disciplines; however, the research literature that documents the success of these strategies may be unfamiliar to many geoscience instructors. This literature review seeks to serve as a bridge that connects the reflective practitioner, the research literature on instructional strategies, and the network of community resources available to the geoscience educator. We review the characteristics of 11 active learning strategies and weigh the evidence that these strategies improve student learning. Furthermore, we analyze the utility of these strategies in the context of their use in geoscience classrooms. We seek to provide geoscience instructors with a decision-making guide and evidence-based recommendations that they can use to select and implement active learning strategies that have the potential to enhance undergraduate learning experiences in geoscience courses.